Rock magnetic properties of Grand Lake sediments as evidence of environmental changes during the last 60 000 years in North‐East Russia. (30th July 2021) - Minyuk, Pavel; Subbotnikova, Tatyana
Abstract : Dansgaard–Oeschger events of the last glacial cycle are widely observed in the North Atlantic sector. In far northeast Asia, however, a lack of data means the presence or absence of these events is uncertain and, if present, the mechanisms that connect this region with the North Atlantic remain unresolved. A sediment record from Grand Lake, North‐East Russia (latitude 60°44′N, longitude 151°53′E), spans much of the last glacial cycle and shows strong variations in magnetic parameters. These variations are related to sedimentation changes that were likely influenced by the palaeoclimate. Rock magnetic properties of a 1020‐cm‐long sediment core were determined for four lithological units. Additionally, samples taken from across the modern catchment aided the interpretation of the magnetic properties of the down‐core sediments. Magnetic minerals in all sediment units consist of detrital, oxidized Ti‐poor titanomagnetites. Sediments of Holocene age (Unit 1) display the lowest values of magnetic susceptibility (MS), saturation magnetization (Js) and saturation remanence (Jrs), and reflect dilution by biogenic silica and organic matter. Variations of magnetic properties in Units 2, 3 and 4, which correspond to Marine Isotope Stages (MIS) 2, 3 and 4, respectively, parallel granulometric changes. Massive sediment structure, which characterizes Unit 3, has a coarser grain size and higher MS, Jrs and Js as compared with the laminated sediments of Unit 2 and Unit 4, suggesting higher‐energy catchment processes. Nine distinct peaks in MS, Js and Jrs within MIS 3 coincide with TiO2 minima and with high pollen percentages of trees and shrubs, supporting the conclusion that lake and catchment sediment processes are associated with fluctuating regional climate. While the dating is not resolved enough to be certain, the data are suggestive that these cycles correlate with Dansgaard–Oeschger events.